N. Krupskaya on the education of conscious discipline - Levanienė , E. (Psichologija, 1971)
The paper treats Krupskaya’s views on the education of conscious discipline. The main principle of discipline training is to draw children into work and into the struggle for the building of a communist society. Work must be collective. Krupskaya highly appreciates the Young Pioneer organization with its clear communist objectives and harmonious structure. Conscious discipline depends on the procedure of work. Undisciplined behaviour is caused not so much by children as by the carelessness of adults. Krupskaya condemns punishment in a children’s collective. Instead of it she suggests explanatory work, checking up of performed tasks, timely help and forestalling of undisciplined behaviour. Group discussion of performed tasks is of great importance as children are taught to analyse their work and to notice its shortcomings and advantages. Thus public opinion is formed and it becomes the main landmark and means of fostering conscious discipline.